Penerapan Data Mining Dengan Algritma Fp-Grwoth Untuk Mendukung Strategi Penjualan Smartphone (Studi Kasus: PT.Oppo Indonesia) - Abigael Martabe Parhusip (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
At present the growing number of smartphones is growing which makes managers want to get a better promotional strategy. The way to find the right sales strategy will be to reduce the cost of promotion and achieve the right sales goals. One way that can be done to determine the promotion strategy is to use data mining techniques. The technique used in this case is the FP-Growth Algorithm. FP-Growth is one alternative algorithm that can be used to determine the set of data that most often appears (frequent item sets) in a data set. FP-Growth algorithm is the development of Apriori algorithm. Whereas in the FP-Growth algorithm no candidate is generated because FP-Growth uses the concept of tree development in searching for frequent itemset. The study was conducted by observing several research variables that are often considered by companies especially in marketing in determining the promotional objectives, namely user objectives, user experience, service, analyst. The results of this study are in the form of a software by implementing the FP-Growth algorithm that uses the concept of FP-Tree development in searching for Frequent Itemset